Techno-Wisdom Synergy: Reinventing Digital Zakat Compliance with Integrating Technology and Local Wisdom - Mardhika Adif, Riandy; Susanto, Perengki; Yumna, Aimatul (Jurnal Aplikasi Manajemen, 2025)
Digital transformation presents both opportunities and challenges in enhancing zakat compliance, particularly in regions with strong cultural and religious values such as West Sumatra. This study aims to analyze the influence of the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), knowledge, trust, and relationship marketing on zakat compliance behavior in the digital era. A quantitative approach was employed through a survey of 286 respondents across five selected districts/cities using cluster sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that positive attitudes toward zakat, subjective norms, perceived behavioral control, ease of use, perceived usefulness, trust, and relationship marketing significantly affect zakat compliance. Knowledge also strengthens the influence of trust and relationship marketing on compliance. The novelty of this study lies in its multidisciplinary integration of technology, social psychology, and marketing within the digital zakat context. The implications provide strategic guidance for zakat institutions to design technology-based policies aligned with local values to increase zakat participation sustainably.